Development of a Co-free, Ni-based alloy layer (Ni-SD) for sealing surfaces of nuclear-power valves cladding by hollow laser beam. (April 2015) - Shi, T.; Fu, G. Y.; Xu, A. Q.; Lu, B. H.
Abstract : To avoid the activated radiation of elemental cobalt and meet the requirements of critical working conditions in which operate the sealing surface of nuclear-power valves, a new cobalt-free Ni-based alloy (Ni-SD) was developed. The powder was deposited on a stainless-steel substrate by a novel hollow laser beam cladding technique. The experimental results reveal that the micro-hardness of Ni-SD can approach 700 HV0·3, which is much higher than that of the common Co-based alloy Stellite6 (500 HV0·3 ) that is currently used in nuclear-power valves. Analytical results indicate that γ -Ni is the primary phase in the Ni-SD coating and that it proportionally dissolves metallic and non-metallic elements. In addition, the Ni-SD coating contains some hard phases, such as carbides and borides. High-temperature measurements indicate that the Ni-SD alloy offers excellent advantages such as high wear resistance and high-temperature operation.